SPECIFICS OF ORGANIZATION OF RURAL TOURISM IN FOREIGN PRACTICE - KALINICHENKO, Sergiy; SPODAR, Kateryna; GRIBINYK, Andrey; KHOLODOK, Valentyna; VYNNYK, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The development of tourism in rural areas is a tool of the redistributive model to reduce the gap between the most backward rural areas and other sectors of the economy. In fact, in many rural areas of Europe, agriculture has ceased to be the most important form of land use and the most important activity of the rural community. In the world tourist practice, recreation in the countryside has long been steadily popular. This is due to the fact that the more people learn about the adverse effects of the urban environment on health, the more popular is the rest in a remote area. International practice shows that the development of rural tourism is a major socio-economic program to transfer part of the agricultural sector from production to services. It should be noted that within rural tourism is practiced and direct production activities: the revival and development of various folk and artistic crafts, traditional handicrafts, production of environmentally friendly products. Rural tourism also allows you to find ways and means to preserve nature. In many countries, the development of this type of tourism has become the main direction of protection and reproduction of national rural landscapes. From the functional point of view, rural tourism is closely related to other types of tourism, especially recreational, cultural, specialized types of tourism - skiing, hunting, fishing, worship and more. was. All this allows to include rural tourism in combined tours, which increases the demand for traditional tourism products. Regardless of the specifics of specific areas, the concept of rural tourism development, in addition to the economic (commercial) context, as a rule, also have a certain ideological meaning. The experience gained by tourists is formed not only in the course of their study of architectural monuments, works of art or folk art, but also through direct contact with the realities of the countryside, as inherent in its inhabitants hospitality, friendliness and friendliness.
Keywords: rural tourism; potential; recreational complex; agrotourism; sphere of tourism